Juridical Analysis of Natural Resource Conservation in the Development of Pahawang Island Lampung Tourism Area Based on Local Wisdom in Indonesia - HANDAYANI, I Gusti Ayu Ketut Rachmi; JAINAH, Zainab Ompu; MARPAUNG, Lintje Anna; RUSLI, Tami; FAIZ, Pan Mohamad (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.v10.5(37).21, 2019)
Pahawang Island is one of the areas that have great tourism potential in Pesawaran Regency, Lampung Province, Indonesia. The issues in this research are what is the regulation of the development of Pahawang Island tourism area and how to regulate the conservation of natural resources in Pahawang Island tourism area. Problem approach is done by normative and empirical juridical, using primary and secondary data as well as qualitative data analysis. Based on the results of research can be concluded that in the development of Pahawang Island tourist area there is no regulation as a guideline, so that society there is no uniformity, in the management of Pahawang Island tourist area. Such as cottage development, dock construction, and observation of marine biota spots. Natural Resources conservation regulation does not yet exist as well, thereby impacting ecosystems that do not reflect real local wisdom. With the regulation in the form of regional regulations, village regulations as the rule of implementing derivative of Law Number 10 of 2009 on Tourism, especially regarding of the Pahawang Island tourist area, making the Pahawang Island and island whose protected management and become an island that can be preserved by indigenous people and migrant according to local wisdom.